Production Cost Efficiency and Production Effectiveness of Small-Scale Bottom Gill Net Fishery Business Every Season in Labetawi Village, Tual City - Picaulima, Simon M.; Rahakbauw, Siska D.; Ngamel, Anna K.; Ohoiwutun, Elisabeth C.; Kilmanun, Anthon D. (Agrikan Jurnal Agribisnis Perikanan, 2023)
Bottom gill net fisheries is a fishery production activity that is highly dependent on the season because changes in wind season patterns largely determine the availability and abundance of fish in a fishing ground, therefore seasonal changes can cause losses to capture fisheries business. Therefore, fisheries production activities must be carried out efficiently and effectively to achieve optimal profits. The study aims to determine the efficiency and effectiveness of bottom gill net fisheries production. The research was conducted from June to September 2023 in Labetawi Village, Difur beach, Tual City. Data were collected using survey methods and determination of responses using census techniques. Data are analyzed in a comparative descriptive manner including fishing ground, amount of production, fixed capital, working capital, production cost efficiency, and production effectiveness delivered in tables and graphs. The results of the analysis showed that optimal profits occurred in the eastern season because of the lowest efficiency of Rp4,053/Kg and the highest effectiveness of 0.000247Kg/Rp, while in transition season 1 it had the lowest effectiveness value of Rp6,539/Kg and the highest efficiency level of 0.000153 Kg/Rp, but in a general bottom gill net fishery production activities were efficient and effective in each season, therefore, the benefits of bottom gill net fisheries could obtain each season with different levels.